2020
DOI: 10.1038/s41598-020-63418-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vectashield-induced fluorescence quenching on conventional and super-resolution microscopy

Abstract: Finding the right combination of a fluorescent dye and a mounting medium is crucial for optimal microscopy of fixed samples. It was recently shown that Vectashield, one of the most commonly used mounting media for conventional microscopy, can also be applied to super-resolution direct stochastic optical reconstruction microscopy (dSTORM). dSTORM utilizes conventional dyes and starts with samples in a fluorescent "ON" state. This helps in identifying structures of interest. Subsequently, labelled samples are in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 27 publications
3
12
0
Order By: Relevance
“…The mechanism of switching, and glycerol’s role thereof, is not known. Another unknown is the cause of the stark reduction in brightness of the fluorophore AF647 in the sulfite switching buffer, similar to what has recently been reported of the Vectashield dSTORM buffer 12 . Once the mechanism behind this behavior is established, it might be possible to find a switching buffer that switches the fluorophore emission as well as sulfite, while maintaining the brightness observed with the primary thiols.…”
Section: Discussionsupporting
confidence: 63%
“…The mechanism of switching, and glycerol’s role thereof, is not known. Another unknown is the cause of the stark reduction in brightness of the fluorophore AF647 in the sulfite switching buffer, similar to what has recently been reported of the Vectashield dSTORM buffer 12 . Once the mechanism behind this behavior is established, it might be possible to find a switching buffer that switches the fluorophore emission as well as sulfite, while maintaining the brightness observed with the primary thiols.…”
Section: Discussionsupporting
confidence: 63%
“…Arsić et al showed the effect of Vectashield, one of the most commonly used mounting media, causing the loss of fluorescence intensity of Alexa Fluor 647 (AF647) via fluorescence quenching . As AF647 blinks in Vectashield, this dye-mounting media combination is often used for dSTORM.…”
Section: Super-resolution Microscopy For Imaging Of Single Cells and ...supporting
confidence: 59%
“…Arsić et al showed the effect of Vectashield, one of the most commonly used mounting media, causing the loss of fluorescence intensity of Alexa Fluor 647 (AF647) via fluorescence quenching. 98 As AF647 blinks in Vectashield, this dye-mounting media combination is often used for dSTORM. However, the authors observed that the fluorescence intensity of AF647 is quenched after mounting immunolabeled samples in Vectashield.…”
Section: Super-resolution Microscopy For Imaging Of Single Cells and mentioning
confidence: 99%
“…The following secondary antibodies were from Thermo Fisher Scientific and diluted 1/1000: goat anti-rabbit IgG Alexa Fluor 488 (A11034), donkey anti-mouse IgG Alexa Fluor 568 (A10037), donkey anti-rabbit IgG Alexa Fluor 568 (A10042) and goat anti-mouse IgG1 Alexa Fluor 647 (A21240). Cells in glass bottom dishes were imaged directly in PBS, whereas cells on coverslips were washed once in water and mounted in VECTASHIELD (unless imaging samples with Alexa Fluor 647, in which case SlowFade Diamond Antifade Mountant (Thermo Fisher Scientific) was used to avoid fluorescence quenching 114 ).…”
Section: Methodsmentioning
confidence: 99%